(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Infertility is often caused by ovulation disorders, among which polycystic ovarian syndrome (PCOS) is clearly the most frequent. Based on the phenotype, ethnicity, and categorization system employed, the incidence of PCOS in the general population ranges from 5% to 15%. Summary Elevated concentrations of androgen, inconsistent menstruation, and/or little cysts on one or both ovaries are all symptoms of PCOS, a complex condition. Therefore, the goal of conventional therapies for PCOS-linked anovulatory infertility is to shift the equilibrium of intraovarian steroid production away from an elevated androgen synthesis caused by LH-insulin-leptin that results in follicular atresia and toward an FSH-driven final advancement of a dominant follicle. There are several therapy possibilities.